3D design of orthotic casts and braces in medical applications. Issue 1 (2nd January 2021) - Venkateswaran, N; Hans, W Jino; Padmapriya, N.
ABSTRACT: Custom-made braces or casts are becoming more prevalent in recent years due to increased comfort and better recovery rates. Modelling these braces require accurate measurement of the limb surface using an imaging device. Modelling of the limb, however, requires a lot of time and the existing technique is quite complex. With the advent of low-cost sensors like the Microsoft Kinect, it is possible to measure RGB and Depth data with sufficient accuracy for 3D modelling applications. By combining data from various views, it is possible to construct a 3D model of the limb. The 3D model is further used for the design of the custom brace or cast using a CAD/CAM model. The system would be cheaper and faster than using an MRI scanner or the traditional Plaster of Paris modelling.